2010
DOI: 10.1055/s-0029-1242983
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Following Endonasal Skull Base Surgery

Abstract: The importance of quality of life (QOL) outcomes following treatments for head and neck tumors are now increasingly appreciated and measured to improve medical and surgical care for these patients. An understanding of the definitions in the setting of health care and the use of appropriate QOL instruments and measures are critical to obtain meaningful information that guides decision making in various aspects of patient health care. QOL outcomes following cranial base surgery is only recently being defined. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(67 citation statements)
references
References 32 publications
4
62
1
Order By: Relevance
“…The same instrument had been evaluated and validated for application to patients who had undergone endonasal surgery. 14 The overall results showed that endoscopic resection of tumors of the anterior and middle skull base preserves health-related QOL measures in most patients. Most of our patients reported that the surgical procedure either improved or did not interfere with their overall QOL.…”
Section: Discussionmentioning
confidence: 92%
“…The same instrument had been evaluated and validated for application to patients who had undergone endonasal surgery. 14 The overall results showed that endoscopic resection of tumors of the anterior and middle skull base preserves health-related QOL measures in most patients. Most of our patients reported that the surgical procedure either improved or did not interfere with their overall QOL.…”
Section: Discussionmentioning
confidence: 92%
“…Pant et al reported on a series of 51 patients undergoing endoscopic surgery who completed the SNOT-22 and ASBQ at 4 postoperative time points. 34 The investigators found that SNOT-22 scores were significantly better at 6 months and 12 months postoperatively as compared with 1-3 months postoperatively. Conclusions from this study are limited by the absence of preoperative data, unspecified distribution of tumor pathology, and a lack of information about the response rate at each time point.…”
Section: Discussionmentioning
confidence: 94%
“…This trend is now well documented with validated outcomes measures and demonstrates the time course of nasal cavity healing. 2,15,19 Symptoms such as nasal congestion and nasal discharge, while troubling to patients, were temporary. Second, we learned that certain intraoperative maneuvers that impact the nasal airway, such as use of absorbable nasal packing and nasal splints used in a minority of patients, were negatively correlated with sinonasal QOL early in the postoperative period (2 weeks to 3 months).…”
Section: Discussionmentioning
confidence: 99%